2015
DOI: 10.1088/0004-637x/812/1/59
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Kinematic Structure of the Outflow/Envelope System of L1527 Revealed by Subarcsecond-Resolution Observation of Cs

Abstract: Subarcsecond-resolution images of the rotational line emissions of CS and c-C 3 H 2 obtained toward the low-mass protostar IRAS 04368+2557 in L1527 with the Atacama Large Millimeter/submillimeter Array are investigated to constrain the orientation of the outflow/envelope system. The distribution of CS consists of an envelope component extending from north to south and a faint butterfly shaped outflow component. The kinematic structure of the envelope is well reproduced by a simple ballistic model of an infalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 55 publications
7
79
0
Order By: Relevance
“…Meanwhile, velocity gradients are also seen in the PV diagram perpendicular to the disk direction (see Figure 8). Such behaviors are consistent with infalling-rotating motion in the envelope (e.g., Sakai et al 2014b;Oya et al 2015Oya et al , 2016, rather than pure rotation in the disk (see also Appendix C). The locations of the most blue and red-shifted emissions then correspond to the innermost radius of such an envelope (indicated by the blue arrows in Figure 6), where all the kinetic energy is converted to rotation (i.e., the centrifugal barrier; Sakai et al 2014a).…”
Section: Envelope/disk Tracerssupporting
confidence: 60%
“…Meanwhile, velocity gradients are also seen in the PV diagram perpendicular to the disk direction (see Figure 8). Such behaviors are consistent with infalling-rotating motion in the envelope (e.g., Sakai et al 2014b;Oya et al 2015Oya et al , 2016, rather than pure rotation in the disk (see also Appendix C). The locations of the most blue and red-shifted emissions then correspond to the innermost radius of such an envelope (indicated by the blue arrows in Figure 6), where all the kinetic energy is converted to rotation (i.e., the centrifugal barrier; Sakai et al 2014a).…”
Section: Envelope/disk Tracerssupporting
confidence: 60%
“…• ; Oya et al 2015), its amplitude distribution shows different profiles along the major-and minor-axes, suggesting a pseudo disk-like envelope, while the envelope of SMM11 is more spherical. These may observationally imply that envelope morphology evolves from spherical shapes into more-disk like shapes.…”
Section: Continuum Visibilitymentioning
confidence: 98%
“…Using ALMA cycle 1 observations, Aso et al (2017) have recently confirmed Keplerian rotation at r < 56 au. The disk of L1527 is nearly edge-on (Tobin et al 2008;Oya et al 2015).…”
Section: L1527mentioning
confidence: 99%